?-Graceful Labeling In the Perspective of Graph Operations on Bistar - Chaurasiya, Mehul; Rupani, Mehul (International Journal of Computer Sciences and Engineering, 2021)
A graceful labelling of a graph G , if a function is an injective function and the induced function is defined by ;where then the resultant edge labels are distinct[3]. Here we discuss about some basic graph like as splitting graph of bistar ,degree splitting graph of bistar ,shadow graph of bistar ,restricted square graph of bistar , barycentric sub division of bistar and corona product ofbistar with K1 admits graceful labelling.